MGPDI: modelo de gestión de la I+D+i en las organizaciones - Weber, Kival; Antonioni, José Antonio; Melchionna, Rosane; Villalobos, María Teresa; Duarte, Ana Marcia; Herbert, Juliana; Machado, Cristina; Machado, Renato; Pereira, Radamés; Schwening, Cristiano (Pontificia Universidad Católica del Perú. Fondo Editorial, 2017)
A strategy to promote innovation in organizations consists of the adoption of Research, Development and Innovation (R+D+I) management systems. This paper aims at describing the current situation of the new R+D+I Management Model (MGPDI) that is applicable to any organization, independently of the size, type and activity. The novelty is in the definition of the: 1) Process Reference Model MR-MGPDI based on innovation best practices and on requirements of the Brazilian ABNT NBR 16501 and the Spanish AENOR UNE 166001-166002 standards; 2) Process Assessment Model MA-MGPDI based on the family of standards ISO/IEC 33000 for process assessment. Until December 2016 there are three goals: 1) to develop, test and publish two MGPDI guides (General Guide and Assessment Guide); 2) train the first implementation consultants, assessors and instructors; 3) perform three pilot of MGPDI implementation and assessment in organizations in southern Brazil, including tests with two online software support tools (SGPDI and MGPDI AA). MGPDI is a process model with great potential of replication in Latin America and Caribbean countries.

Una estrategia para promover la innovación en las organizaciones consiste en la adopción de sistemas de gestión de la investigación, desarrollo e innovación (I+D+i). El objetivo de este artículo es describir la situación actual del nuevo modelo de gestión de I+D+i (MGPDI) que es aplicable a cualquier organización, independientemente del tamaño, tipo y actividad. La novedad está en la definición del: 1) modelo de referencia MR-MGPDI, basado en buenas prácticas de innovación y en los requisitos de las normas ABNT NBR 16501 y AENOR UNE 166001-166002; y 2) modelo de evaluación MA-MGPDI, basado en la familia de normas ISO/IEC 33000 de evaluación de procesos. Hasta diciembre de 2016, hay tres objetivos: 1) desarrollar, probar y publicar dos guías MGPDI (Guía general y Guía de evaluación); 2) capacitar a los primeros consultores de implementación, evaluadores e instructores; y 3) realizar tres implementaciones y evaluaciones piloto del MGPDI en organizaciones del sur de Brasil, incluyendo el soporte de dos herramientas de software en línea (SGPDI y MGPDI AA). MGPDI es un modelo de proceso con un gran potencial de replicación en los países de América Latina y el Caribe.
Keywords: Investigación; Desarrollo; Innovación; I D i; Modelo de gestión; https://purl.org/pe-repo/ocde/ford#5.02.04